2001
DOI: 10.1186/1471-2121-2-17
|View full text |Cite
|
Sign up to set email alerts
|

MP20, the second most abundant lens membrane protein and member of the tetraspanin superfamily, joins the list of ligands of galectin-3

Abstract: Background: Although MP20 is the second most highly expressed membrane protein in the lens its function remains an enigma. Putative functions for MP20 have recently been inferred from its assignment to the tetraspanin superfamily of integral membrane proteins. Members of this family have been shown to be involved in cellular proliferation, differentiation, migration, and adhesion. In this study, we show that MP20 associates with galectin-3, a known adhesion modulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…MP20, a member of the tetraspanin superfamily, is the most abundant integral membrane protein of lens fiber cells, which appears to be distributed uniformly in the plasma membrane but also occurs in distinct membrane junctional domains early during embryonal development [ 9 , 28 - 30 ].Mutations in MP20 severely disrupt normal crystalline fiber cell arrangement in the lens and cause cataractogenesis [ 7 , 8 , 31 ]. Tetraspanins form contacts with other cells or the extracellular matrix by binding to other tetraspanins, to adhesion receptors such as integrins, and to extracellular proteins [ 32 - 34 ]; in this context, recently MP20 and galectin-3 were identified to co-localize in selected areas of the cell plasma membrane and biochemical analysis confirmed that MP20 and galectin-3 interact with each other [ 11 ]. In fact, galectin-3 is a multifunctional protein, which occurs early during embryonal development, with reported involvement in development, oncogenesis, and inflammation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MP20, a member of the tetraspanin superfamily, is the most abundant integral membrane protein of lens fiber cells, which appears to be distributed uniformly in the plasma membrane but also occurs in distinct membrane junctional domains early during embryonal development [ 9 , 28 - 30 ].Mutations in MP20 severely disrupt normal crystalline fiber cell arrangement in the lens and cause cataractogenesis [ 7 , 8 , 31 ]. Tetraspanins form contacts with other cells or the extracellular matrix by binding to other tetraspanins, to adhesion receptors such as integrins, and to extracellular proteins [ 32 - 34 ]; in this context, recently MP20 and galectin-3 were identified to co-localize in selected areas of the cell plasma membrane and biochemical analysis confirmed that MP20 and galectin-3 interact with each other [ 11 ]. In fact, galectin-3 is a multifunctional protein, which occurs early during embryonal development, with reported involvement in development, oncogenesis, and inflammation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It encodes an abundant integral lens membrane protein MP20 which is a new regulatory protein important for mammalian lens fiber cell junctional formation [ 9 ]. Lens-specific MP20 is classified as a member of the PMP22/EMP/MP20 subfamily of tetraspanins [ 10 ] and adds to a growing list of ligands of galectin-3[ 11 ], a known adhesion modulator that is expressed by microglial cells of adult brain [ 12 ] and contributes to injury in the deep gray matter areas of the brain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lim2 is present throughout the lens fibre membrane [70,71], where it is believed to interact with galectin 3 [72], a known facilitator and modulator of cellular adhesion [73]. Finally, in mice deficient in Lim2, the fibre mass is readily dissociated into individual cells [62], suggesting a defect in intercellular adhesion (see also figure 8).…”
Section: Intercellular Junctions and Adhesion Proteinsmentioning
confidence: 99%
“…The notion that Lim2 could also be an adhesive protein is based on the recognition that Lim2 is a member of a family of adhesion-related proteins that includes claudins and peripheral myelin protein 22 [62]. Lim2 is present throughout the lens fibre membrane [70,71], where it is believed to interact with galectin 3 [72], a known facilitator and modulator of cellular adhesion [73]. Finally, in mice deficient in Lim2, the fibre mass is readily dissociated into individual cells [62], suggesting a defect in intercellular adhesion (see also figure 8).…”
Section: Intercellular Junctions and Adhesion Proteinsmentioning
confidence: 99%
“…Therefore, the reported urea-induced destabilization of the AMPA-R is a phenomenon observed in a very specific experimental system. It is important to note that 4 M urea wash of the membrane is an effective approach in improving the purity and quality of other membrane proteins, such as gap junction connexins and aquaporins [ 100 102 ]. In addition, vesicles that were washed with KI maintain their ability to bind to molecular motors and thus can be used for in vitro motility assays, suggesting that motor acceptors on the vesicles are unaffected by the KI wash [ 103 ].…”
Section: Biochemistry Of Endogenous Ampa Receptorsmentioning
confidence: 99%